2022
DOI: 10.1109/access.2021.3138753
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Cryptography-as-a-Service for Secure UAV Communication: Applications, Challenges, and Case Study

Abstract: The sudden demand rises in security made researchers come up with solutions that provide instantaneous safety better than the state of the art solutions. The quest for securing data began in the Spartan era. People are now looking to expand this field of research by attacking the existing paradigms and inventing new algorithms that prove to be better than their vulnerable counterparts. Unmanned aerial vehicles (UAVs) are very much prevailing due to their sleek design and flexible mobility in many sectors such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…A backscatter transmitter emits and backscatters the signal photon, while the idler photon is retained at the receiver. The QBC configuration improves the communication channel's error exponent significantly and enables secure communication through quantum cryptography [163].Traditional security methods such as encryption and digital signatures may not be viable for a swarm of UAVs due to power and complexity constraints. On the other hand, this technology is not intended for large-scale deployment of low-power UAV networks, which often include a diverse set of devices and is one of the primary goals of 6G mobile networks.…”
Section: J Quantum Backscatter Communicationsmentioning
confidence: 99%
“…A backscatter transmitter emits and backscatters the signal photon, while the idler photon is retained at the receiver. The QBC configuration improves the communication channel's error exponent significantly and enables secure communication through quantum cryptography [163].Traditional security methods such as encryption and digital signatures may not be viable for a swarm of UAVs due to power and complexity constraints. On the other hand, this technology is not intended for large-scale deployment of low-power UAV networks, which often include a diverse set of devices and is one of the primary goals of 6G mobile networks.…”
Section: J Quantum Backscatter Communicationsmentioning
confidence: 99%
“…GNSS spoofing threats were evaluated in Schmidt, et al [9] and concluded that even though spoofing currently might be hard to carry out in the field, the low-cost GNSS jammers indicate that eventually similarly low-cost GNSS spoofers will be developed. The need for balance between the security level of cryptography protocols and their requirement for computational power resources can be seen in Ralegankar, et al [10].…”
Section: Related Work and Literature Reviewmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs), on the other hand, are seen as a potential asset due to their broader application in scope [136]. A number of communication protocols are needed to support the successful flight of UAVs.…”
Section: E-votingmentioning
confidence: 99%
“…Blockchain scalability [101] Decentralization using quantum blockchain [99] Auction on quantum blockchain [97] Quantum-based privacy-preserving auction [98] Quantum e-payment protocol [91] Quantum NFT for blockchain [57] A novel e-payment protocol [92] Crypto-currency system with QKD [57] Quantum digital signature [75] Blockchain cryptography resistant to quantum computing attacks [22] Smart contract based on quantum blind signature [59] Logic programming for smart contract [62] Consensus based on post-quantum signature [49] Quantum-enhanced logic-based blockchain [45] A stake vote consensus algorithm [7] Post-quantum blockchain for a scalable smart city [125] Blockchain in the quantum world [8] Quantum-secured blockchain [11] Anti-quantum attribute-based signature [106] Quantum cryptography-as-a-service [136]…”
mentioning
confidence: 99%